Cina-Surabaya Dialect Spoken to Younger, Same Age, and Older Addressees in Surabaya - Fadillah, Khalis (Bina Nusantara University, 2018)
This research focused on the way Tionghoa ethnic people used Cina-Surabaya as the dialect produced by them to speak to a younger, same age, and older addressee. Looking at the differences on how Cina-Surabaya dialect used for the different age gap, the problems of the research were differences in how Tionghoa ethnic people used Cina-Surabaya dialect and how Tionghoa ethnic people used Cina-Surabaya dialect to speak for different age gap. In this research, the researcher applied the descriptive qualitative method with four steps; they were recording the data, organizing the data, transcribing the data, and summarizing or interpreting the findings. The result shows that their dialect has a different pattern in their utterances based on the addressee they are talking. On the linguistics features, they add some prefix and suffixes from the original Javanese language and take it as their language in expressing several words.